2022
DOI: 10.1016/j.aace.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Branchial Cleft Remnant Masking as a Thyroid Mass in an Adult Patient

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…7 Two additional cases under visual vignettes highlighted the differential diagnosis of thyroid/neck masses due to hyperplastic thyroid nodule within the remnant pyramidal lobe and branchial cleft remnant. 8,9 On Diabetes, Lipid, and Metabolism, authors reported on two genetically confirmed cases of Wolfram Syndrome, a rare endoplasmic reticulum disorder characterized by insulin-dependent diabetes mellitus, optic nerve atrophy, and progressive neurodegeneration. Highlighting the importance of considering monogenic diabetes genetic testing, including WFS1 gene, for patients with early-onset diabetes who are negative for islet autoantibodies and lean in order to offer proper management and improved quality of life in patients with this rare medical condition.…”
mentioning
confidence: 99%
“…7 Two additional cases under visual vignettes highlighted the differential diagnosis of thyroid/neck masses due to hyperplastic thyroid nodule within the remnant pyramidal lobe and branchial cleft remnant. 8,9 On Diabetes, Lipid, and Metabolism, authors reported on two genetically confirmed cases of Wolfram Syndrome, a rare endoplasmic reticulum disorder characterized by insulin-dependent diabetes mellitus, optic nerve atrophy, and progressive neurodegeneration. Highlighting the importance of considering monogenic diabetes genetic testing, including WFS1 gene, for patients with early-onset diabetes who are negative for islet autoantibodies and lean in order to offer proper management and improved quality of life in patients with this rare medical condition.…”
mentioning
confidence: 99%